2013
DOI: 10.3382/ps.2013-03208
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk factors associated with contact dermatitis, lameness, negative emotional state, and fear of humans in broiler chicken flocks

Abstract: The objectives of this study were to 1) identify determinants of poor welfare in commercial broiler chicken flocks by studying the associations between selected resource-based measures (RBM, potential risk factors), such as litter quality and dark period, and animal-based welfare indicators (ABM), such as foot pad dermatitis and lameness, and 2) establish the breadth of effect of a risk factor by determining the range of animal welfare indicators associated with each of the risk factors (i.e., the number of AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 57 publications
8
71
0
3
Order By: Relevance
“…However, the early date of some of our farm visits (up to 10 days before slaughter) and our modest sample size may have decreased our chances of finding associations. We did confirm the association between litter quality and dermatitis reported by Bassler et al (2013). Models on the criterion level allowed a reduction in assessment time of~1 h, by making the 'dust', 'breast blister' and 'lameness' measure redundant.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, the early date of some of our farm visits (up to 10 days before slaughter) and our modest sample size may have decreased our chances of finding associations. We did confirm the association between litter quality and dermatitis reported by Bassler et al (2013). Models on the criterion level allowed a reduction in assessment time of~1 h, by making the 'dust', 'breast blister' and 'lameness' measure redundant.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have suggested a correlation between dermatitis and plumage cleanliness (Arnould and Colin, 2009;De Jong et al, 2015) or litter quality (Bassler et al, 2013), but these studies differ considering a possible correlation between dermatitis and lameness. Thus, the stability of such correlations still needs confirmation.…”
Section: Introductionmentioning
confidence: 98%
“…Among the common risk factors, we are inclined to add fast-growing broiler flocks, the age at which they are slaughtered, etc. (de Jong et al 2012;Bassler et al 2013;Tullo et al 2017). With regards to the findings of Greene et al (1985), namely that breast and tarsometatarsal lesions were of economic significance, we believe that PPD, leading to a worsened welfare of the flock, is also related to a loss of produce for poultry farmers.…”
Section: Discussionmentioning
confidence: 88%
“…The mean prevalence of broilers displaying a gait score of 3 or above has previously been reported to be between 15 and 55% (Kestin et al 1992;Sanotra et al 2001;Knowles et al 2008). More recently, studies conducted across multiple flocks, farms and countries have reported the prevalence of birds with a moderate to severe gait impairment (gait score 3 or above) to be between 5.5 and 48.8% (Bassler et al 2013;Tahamtani, Hinrichsen and Riber 2018;Kittelsen et al 2017;Granquist et al 2019).…”
Section: Walking Abilitymentioning
confidence: 99%